Experimental optimization of voltage stability and power output in PMDC micro-hydropower systems using a buck–boost converter - Firdiansyah Firdiansyah; Indrayani Indrayani; Rusdianasari Rusdianasari (Politeknik Negeri Lhokseumawe, 2026)
Low-head micro-hydropower systems often experience voltage instability due to fluctuating water flow and low turbine rotational speeds, limiting their ability to supply reliable power to standalone electrical loads. This study aims to experimentally optimize the output performance of a permanent magnet DC (PMDC) generator integrated with a buck–boost DC-DC converter in a low-head micro-hydropower system for improved voltage regulation, power output, and system efficiency. Experiments were performed by varying the generator rotational speed from 29.83 to 144.80 RPM with a 30 W LED load, while the converter maintained a constant 14.6 V set-point. Measured parameters included generator input voltage, input current, regulated output voltage, load current, electrical power, and system efficiency. The experimental results show that the system can operate at an ultra-low input voltage of 3.61 V at 29.83 RPM. The optimal operating condition was achieved at 63.78 RPM, where the system reached a maximum efficiency of 74.7% and an output power of 27.7 W. The converter maintained a stable output voltage close to the required load voltage, within the rotational speed range of 68.20-132.40 RPM. These results demonstrate that integrating a PMDC generator with a buck-boost converter improves voltage stability and expands the usable operating range of low-head micro-hydropower systems, making the proposed configuration suitable for off-grid and rural electrification applications.